Proveniência das rochas metassedimentares do Cinturão Araguaia com base em datações Pb-Pb em zircão e idades-modelo Sm-Nd - PINHEIRO, Bruno Luís Silva (2015)
This paper presents single zircon Pb-evaporation ages, obtained in detrital zircon grains, and Sm-Nd (TDM) for metassedimentary rocks of the Araguaia belt, to investigate the possible source areas of these rocks, and to contribute to understanding the geologic evolution of this belt in the context of the West Gondwana amalgamation. Quartzite of the Morro do Campo Formation, located in the north segment of the belt (Xambioá region) gave Archean 207Pb/206Pb zircon ages (2.65-3.0 Ga), while in the south segment (Paraíso do Tocantins region), the 207Pb/206Pb zircon ages were mainly Meso-Neoproterozoic (1.25-0.85 Ga), and, secondarily, Paleoproterozoic (1.85-1.70 Ga). These results suggest the existence of different sources areas for this quartzite. The Sm-Nd (TDM) model ages of metapelites (slate, phyllite and micaschist) present bimodal distribution with the main population occurring between 2.1 and 1.4 Ga (mode in 1.6-1.7 Ga), and a less abundant population between 2.7 and 2.4 Ga. These data have been interpreted as mixing of Paleoproterozoic (or even Archean) sources with younger, probably Meso-Neoproterozoic, sources. The main candidates to be the sources of the metassedimentary rocks of the Araguaia belt would be those crustal segments located in the southeastern (São Francisco Craton, Goiás Massif, Goiás Magmatic Arc). The sedimentary succession deposited in the Araguaia oceanic basin and the associated magmatic rocks were transported, later, towards the east margin of the Amazonian Craton, during the main tectonic that led to the structural development of the Araguaia belt as a result of the West Gondwana amalgamation.